Reasons for failure of mandibular advancement splint therapy in the treatment of obstructive sleep apnea - Palotie, Tuula (TAYLOR & FRANCIS LTD, 2025)
Objective: To investigate the reasons for poor adaptation to mandibular advancement splint (MAS) treatment.
Methods: The study consisted of 44 patients with obstructive sleep apnea who had unsuccessful MAS treatment. Data were collected on age, body mass index, gender, general and mental diseases, continuous positive airway pressure (CPAP) tryout, usage of occlusal splint, dental overjet, temporomandibular disorders, shortened dental arch, sleep apnea severity, and Apnea-Hypopnea Index. Sixty patients who underwent successful MAS treatment were controls.
Results: Patients with missing molars failed significantly more often in MAS therapy than the controls (p = 0.020). Patients with CPAP tryout prior to MAS treatment had a tendency to fail MAS treatment. MAS treatment was more likely to be successful in patients with prior occlusal splint experience (p = 0.050).
Conclusion: The study could not identify a single reason for MAS failure.